Effect of fiber content on mechanical performance and cracking characteristics of ultra-high-performance seawater sea-sand concrete (UHP-SSC) - Huang, Bo-Tao; Wang, Yu-Tian; Wu, Jia-Qi; Yu, Jing; Dai, Jian-Guo; Leung, Christopher KY (Advances in structural engineering, 2021)
Developing seawater sea-sand concrete can address the challenges arising from the lack of freshwater and river/manufactured sand for making concrete on-site for sustainable marine and coastal construction. To eliminate the corrosion risk of steel fibers while maintaining the high ductility of concrete, this study aims to develop a new type of ultra-high-performance seawater sea-sand concrete (UHP-SSC) by using ultra-high-molecular-weight polyethylene fibers. The effect of fiber content (0%, 0.5%, 1.0%, and 1.5% by volume) on the mechanical performance and cracking characteristics of UHP-SSC was experimentally investigated. The results showed that as the fiber content increases, the tensile strength and strain capacity of UHP-SSC significantly increase, while the compressive strength slightly decreases (but still over 130 MPa). The stochastic nature of the crack width was characterized by the Weibull distribution. A probabilistic model was used to model the evolution of the crack width for UHP-SSC at different strain levels. The model showed good agreement with the experimental results, and it can be used to estimate the allowed tensile strain of UHP-SSC in practical applications for a given limit of crack width and cumulative probability. The findings in this study provide insights into the future design of UHP-SSC in marine and coastal applications.